Crystal Anharmonicity in Strontium Monochalcogenides - Kumar, Raj; Singh, Devraj; Tripathi, Sudhanshu (Asian Journal of Chemistry, 2012)
This paper describes the temperature dependence of the ultrasonic velocities of Strontium chalcogenides SrX (X: S, Se and Te) for longitudinal and shear waves along <100>, <110> and <111> crystallographic directions in the temperature range 100-500 K. The second- and third- order elastic constants have also been evaluated for these chalcogenides using Coulomb and Born-Mayer potential. The second and third order elastic constants are used to find out ultrasonic velocities. The values of elastic constants and ultrasonic velocities are highest for SrS. Hence the mechanical properties and crystallography of SrS are better than SrSe and SrTe. Obtained results are discussed and compared with available results of same type of materials.